Anticipation of cognitive conflict is reflected in microsaccades: Evidence from a cued-flanker task - Mario Dalmaso; Luigi Castelli; Giovanni Galfano (Bern Open Publishing, 2019)
Microsaccade frequency has recently been shown to be sensitive to high-level cognitive processes such as attention and memory. In the present study we explored the effects of anticipated cognitive conflict. Participants were administered a variant of the flanker task, which is known to elicit cognitive interference. At the beginning of each trial, participants received a colour cue providing information about the upcoming target frame. In two thirds of the trials, the cue reliably informed the participants that in the upcoming trial the flankers either matched the central target letter or not. Hence, participants could accurately anticipate whether cognitive conflict would arise or not. On neutral trials, the cue provided no useful information. The results showed that microsaccadic rate time-locked to cue onset was reduced on trials in which an upcoming cognitive conflict was expected. These findings provide new insights about top-down modulations of microsaccade dynamics.